A longitudinal analysis of the relationship between cultural adaptation and argumentativeness. Issue 1 (15th December 2017) - Croucher, Stephen Michael; Kelly, Stephanie; Condon, Shawn Michael; Campbell, Elsa; Galy-Badenas, Flora; Rahmani, Diyako; Zeng, Cheng; Nshom, Elvis
Abstract : Purpose: This study aims to first explore the extent to which argumentativeness changed during the adaptation process among Muslim immigrants to France from 2006 to 2015 and, second, to examine the cultural fusion process. The study investigates the influence of intercultural contact on communication traits by exploring the extent to which members of the dominant cultural group adapt their argumentativeness over time. Design/methodology/approach: Through a longitudinal panel study, the paper investigates the influence of intercultural contact on communication traits by exploring the extent to which members of the dominant cultural group adapt their argumentativeness over time. Confirmatory factor analysis and structural equation modeling are used to assess the hypotheses and research question. Findings: Results revealed a curvilinear relationship between argumentativeness and time. Argumentativeness increased from 2006 to 2009, remained constant from 2009 to 2012 and then decreased after 2012. Furthermore, data analysis revealed argumentativeness levels among members of the dominant culture did not change. Research limitations/implications: The results are potentially limited by the sample being a convenience sample and the presence of extenuating factors. Originality/value: Argumentativeness is viewed by many researchers as a functional form of communication. However, few studies have longitudinally studied how this trait can change over time.